STRATEGI KOMUNIKASI EFEKTIF UNTUK LAYANAN PERPUSTAKAAN PERGURUAN TINGGI - Marta, Revi (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
College Libraries have various ways to communicate with users. This article describes how to communicate information and services effectively in the library field, especially the relationship between librarians and users. Another main focus of this article is assessing what the library wants to communicate and interact with. This article will present a summary of the communication styles that form the basis of librarian communication skills. College-level libraries must build strong social relationships with their academic communities in order to serve them in the most effective way, especially in an environment where resources are limited. In addition, this article also examines various forms of communication between library staff and library users in library services